Penerapan Metode âEarn Valueâ Dan âProject Crashingâ Pada Proyek Konstruksi: Studi Kasus Pembangunan Gedung IGD RSUD Sunan Kalijaga, Demak - Priyo, Mandiyo; Zhafira, Talitha (Semesta Teknika, 2017)
Project of construction have unique characteristic. Process os construction will not continued by the other project. It caused by the condition that affect by the other project. The controlling of project is required to maintain compatibility between planning and actuating. Every activity that held in project must be do inspection and checking with spesification that used. The aim of the researchis determine the performance of project in terms of time and fixed cost. Beside that, This research intend to estimate time and cost for finishing project, and determining project performance index. Data that used for this is secondary data. Secondary data are obtained from contractor. There are budget plan, weekly report, progress report, and fixed cost of project. Research methode that used is Earned Value Methode. It could be analysis from schedulling, cost, and visualisation achievement jobs. From this methode is obtained estimation of cost and time to finishing project. This analysis is done by software Microsoft Excel.2010. Based on 19th week, The result show that have planned Value (PV) sebesar Rp.3.981.025.497,26, nilai Earned Value sebesar Rp. 4.835.552.298, dan nilai Actual Cost sebesar Rp.3.409.775.000,00. Based on Cost Varian sebesar Rp. 1.425.777.298,00 dan Cost Performance Index = 1,418 that the project have profit. From the schedulling project aspect is accelerating 5 week from the project schedule planning. It shows by the schedule varians Rp. 854..526.800,74 and schedule performance indeks = 1,215. Estimating cost to finishing project is Rp 4.950.908.465,70.